1988
DOI: 10.1159/000234603
|View full text |Cite
|
Sign up to set email alerts
|

Allergenic Cross-Reactivity between <i>Callistemon citrinis</i> and <i>Melaleuca quinquenervia</i> Pollens

Abstract: Aqueous extracts of both Callistemon citrinis (bottlebrush) and Melaleuca quinquenervia (melaleuca) were analyzed for allergenic cross-reactivity. Inhibition analysis using the radioallergosorbent test (RAST) was performed on the ammonium bicarbonate extracts of bottlebrush (NH4B) and melaleuca (NH4M) pollens. RAST inhibition analysis demonstrated that the extracts contained allergenically cross-reactive components. Sephadex G-100 column chromatography of NH4B and NH4 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(21 reference statements)
1
1
0
Order By: Relevance
“…Regardless of which extract was analyzed for antigenic as well as allergenic cross-reactivity, the studies reported here and previously [1,2] strongly suggest the existence of immunological cross-reactivity among the three pollens.…”
Section: Discussionsupporting
confidence: 56%
“…Regardless of which extract was analyzed for antigenic as well as allergenic cross-reactivity, the studies reported here and previously [1,2] strongly suggest the existence of immunological cross-reactivity among the three pollens.…”
Section: Discussionsupporting
confidence: 56%
“…Cross-reactivity between closely related species has been well documented for grasses [12,17,18] and trees [17,19,20]. Cross-reactivity between unrelated species seems much rarer, but Howlett et al [21] demonstrated cross-reactivity between Acacia and ryegrass pollen allergens using RAST inhibition stud ies similar to those applied here.…”
Section: Discussionmentioning
confidence: 52%